Usability Evaluation and Recommendations for the Notion Application to Enhance Student Productivity - Matte, Karenina Cornelia Martines; Latuperissa, Rudy (Sistemasi: Jurnal Sistem Informasi, 2025)
This study was conducted to assess the usability level of the Notion application using the USE (Usefulness, Satisfaction, and Ease of Use) Questionnaire and the Cognitive Walkthrough method. These methods were selected due to their proven effectiveness in generating accurate and relevant data for usability evaluation. By employing both the USE Questionnaire and the Cognitive Walkthrough, this research provides development recommendations aimed at optimizing Notion’s ability to enhance student productivity. The sample was determined using Slovin's and Nielsen's formulas, involving 100 student users of the Notion application in Indonesia and 3 active IT students as evaluators. The research instrument utilized a questionnaire based on a 4-point Likert scale. The results indicate that Notion has a relatively high level of usability in supporting student productivity. However, the study identified several usability weaknesses, particularly in the variables of Ease of Use, Ease of Learning, as well as in Task Scenario 1, Task Scenario 3, and Task Scenario 6.